The Effective and Creative Method to Teach Environmental Care Attitudes for Early Childhood - Fadlilah, Azizah Nurul; Muqowim, Muqowim (Universitas Negeri Semarang, 2020)
Garbage is still a big problem for the world, especially Indonesia. The continual increase in waste production and the lack of environmental care are the cause of this problem. It is very important to teach attitudes of environmental care started in early age. Therefore, teachers should be able to find the right methods to make the students have an environmental care. The purpose of this research is to present the Method of Sampah Berkah used in TK Al-Huda Malang City in an effort to teach attitudes of environmental care for students. This research used a qualitative approach with descriptive analysis methods. Data collection techniques are observation and in-depth interviews. The results showed that Sampah Berkah can be an effective and creative method to teach environmental care attitudes for early childhood. Through this Sampah Berkah, children are trained to sort, give and use garbage for recycling, in order that garbage is not immediately thrown away. So, the child's environmental caring attitudes can grow and develop.